DOES FEDERAL ACCOUNTING AND AUDITING NEED OVERHAULING? - Harris, Joseph P. (The Accounting Review, 1940)
Abstract It goes without saying that the Federal government because of the huge size of its annual budget needs to utilize the most approved, modern, and scientific systems of accounting, financial reporting, and auditing. Methods, which were reasonably satisfactory years ago when expenditures were relatively small, may be wholly inadequate today. The present financial administration of the Federal government was subject to strong criticism in the reports of the committees of the U.S. Congress and the President on government reorganization in 1937. There is serious need for the improvement of the accounting, reporting, and auditing of the Federal government. The evidence indicates that in many respects the accounting methods and practices are not up-to-date, and do not provide the essential financial data to the departmental executive officers, the President, the United States Bureau of the Budget, the Congress and to the public. The improvement of the accounting systems of the departments and bureaus will require constant and continued expert attention and study. The road to such improvement would appear to lie in building in each major governmental unit a competent accounting office, headed by a trained and experienced accountant, who is made responsible for departmental accounting.